Exposure to volatile organic compounds is a risk factor for diabetes retinopathy: a cross-sectional study - Wang, Zhi; Chen, Dongjun; Peng, Lingling; Wang, Xian; Ding, Qun; Li, Liang; Xu, Tongdao (Frontiers in Public Health, 2024)
Introduction A few past experimental studies have indicated that exposure to volatile organic compounds (VOCs) might be a potential risk factor for diabetes retinopathy (DR). However, these findings lack substantial support from extensive epidemiological research. This large-scale cross-sectional study aimed to examine whether exposure to low levels of VOCs in the general population is associated with diabetes mellitus (DM) and DR. Methods The analytical data was from the National Health and Nutrition Examination Survey (NHANES) dataset (2011–2018). To minimize the potential impact of gender and age on the findings, propensity score matching was utilized to align the data selection. Relationships between blood VOCs and DM and DR were assessed in a sample of 2,932 adults using the logistic regression models. Additionally, Bayesian kernel machine regression (BKMR) models and Weighted Quantile Sum (WQS) were conducted for mixture exposure analysis. Results The result shows VOCs were positive associated with DM and DR in US adults, as assessed by WQS model, and the calculated odd ratios (ORs) [95% confidence interval (C.I)] were 53.91(34.11 85.22) and 7.38(3.65 14.92), respectively. Among the components of VOCs, 1,2-Dibromoethane, Carbon Tetrachloride and 2,5-Dimethylfuran were positive related with the DR, and ORs (95%C.I) were 2.91(2.29 3.70), 2.86(2.25 3.65) and 2.19(1.79 2.94), respectively. BKMR model shows that there was a dose–response relationship between combined VOCs and DR, although the relationship was non-linearly. Conclusion This study suggested that exposure to VOCs may increase the risk of DR, which had important public health implications.